METAMORPHOSIS OF LEXICAL FEATURES OF SPEECH IN THE COURT INVESTIGATION TRANSLATION - ISOLAHTI, Nina (Comparative Legilinguistics, 2017)
The article deals with the speaker‘s lexicon features during court interpretation. The study is based on the transcripts of the authentic interpreter mediated court investigations and analyzed using a corpus analytical approach. The analysis of the data shows, that interpreters strive to be loyal to the juristic macrocontext and the situation in which conversation takes place. That might lead to the wrong understanding of the identity (personality) of the speaker by the recipient. The overemphasizing of the features of speakers idiolect might lead to major misrepresentation of the information that was in the source message. The interpreter's endeavor of using special juristic terms might also complicate communication process.